2020
DOI: 10.1177/0268355520932410
|View full text |Cite
|
Sign up to set email alerts
|

Study of association of varicose veins and inflammation by inflammatory markers

Abstract: Objective In varicose veins, increased levels of inflammatory markers are indicators of endothelial damage and increased procoagulant activity. These findings support the assumption that the constitution of blood in varicose veins differs from that of systemic blood. The purpose of the study was a correlative study of blood constituents in varicose veins and peripheral veins (normal vein) in same individual with varicose vein which was done by comparing the level of concentration of interleukin-6, fibrinogen, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The same group also looked into the various inflammatory markers. Blood withdrawn from the site of varicose vein appears to have significantly increased concentration of interleukin-6, fibrinogen, and hemoglobin when compared to same patient's antecubital venous blood sample supporting the hypothesis of greater inflammation in tissues drained by varicose veins [16].…”
Section: Varicose Veinsmentioning
confidence: 66%
“…The same group also looked into the various inflammatory markers. Blood withdrawn from the site of varicose vein appears to have significantly increased concentration of interleukin-6, fibrinogen, and hemoglobin when compared to same patient's antecubital venous blood sample supporting the hypothesis of greater inflammation in tissues drained by varicose veins [16].…”
Section: Varicose Veinsmentioning
confidence: 66%
“…However, it should be noted that the current study was a case–control study, which could not determine the time sequence of changes in inflammatory indicators and the formation of venous ulcers. Previous studies have shown that inflammation was increased in blood tissues drained by varicose veins without ulceration 42,43 . We speculated that changes in inflammatory indicators might be related to the formation of venous ulcers, but venous ulcers might further influence changes in inflammatory indicators, especially when accompanied by infection.…”
Section: Discussionmentioning
confidence: 88%
“…Previous studies have shown that inflammation was increased in blood tissues drained by varicose veins without ulceration. 42,43 We speculated that changes in inflammatory indicators might be related to the formation of venous ulcers, but venous ulcers might further influence changes in inflammatory indicators, especially when accompanied by infection.…”
Section: Discussionmentioning
confidence: 99%
“…Slow blood flow, or blood stagnation in varicose veins, leads to hypoxia and inflammation within the vessel wall. Blood samples collected from varicose veins showed an increased concentration of interleukin-6, fibrinogen, and hemoglobin in comparison with blood samples from the antecubital vein of the same patient [ 29 ]. Under these conditions, purine metabolism begins with ATP and ends with hypoxanthine and xanthine.…”
Section: Discussionmentioning
confidence: 99%